ANALISIS SELF CONFIDENCE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK PADA MATERI BARISAN DAN DERET - Zenal Muh Ramdan; Liana Veralita; Euis Eti Rohaeti; Ratni Purwasih (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study aims to determine the relationship between self confidence on the mathematical problem-solving abilities of students of SMK on the sequence and series material. The method in this research is descriptive qualitative. The place of research conducted at SMK Al-Ibrohimiyah Cianjur academic year 2018/2019 class XII Administration Offices with the number of 17 students. The instruments in this research are self confidence scale questionnaire and math solving ability test. Analysis of data used in this study using SPSS 21.00 with product moment analysis to measure the relationship of self confidence to the ability of problem solving mathematically. Based on the calculation, the result of data analysis shows that there is a correlation coefficient (r) of 0.784 with p = 0,000 (p <0.01) which means there is a significant positive relationship between self confidence on the ability of problem solving mathematically. This means that self confidence covering the aspects that exist in it can be used as a predictor to measure the ability of problem solving mathematically, the higher the self confidence of students, the students have good problem solving skills, otherwise the lower the students' self confidence, the students has a poor problem solving ability.